Autores - Rivas, Ramón D. (Kóot, 2021)
José Óscar Batres Posada Alejandro Hartmann Matos Ana Cecilia Vilá de Lara Salvador Marroquín Melissa Regina Campos Solórzano Juanita Santos Moreno Jorge Rolando García Perdigón Carmen Molina Tamacas